Jerusalén y el cristianismo - Khoury, Geries S. (Revista de Estudios Árabes, 2014)
The author reminds the reader that Christianity originated from Jerusalem and throughout the centuries spread to all continents. Christianity rightful claim over the city is justified by the fact that Jesus Christ’s three years of public life and His subsequent crucifixion happened in the Holy City. Modern times Jerusalem is subject of religious discrimination imposed by the occupying forces. The only solution for the three monotheistic religions is mutual tolerance and sharing.